2009
DOI: 10.1038/sj.bjc.6605328
|View full text |Cite
|
Sign up to set email alerts
|

Koilocytes indicate a role for human papilloma virus in breast cancer

Abstract: BACKGROUND: High-risk human papilloma viruses (HPVs) are candidates as causal viruses in breast cancer. The scientific challenge is to determine whether HPVs are causal and not merely passengers or parasites. Studies of HPV-related koilocytes in breast cancer offer an opportunity to address this crucial issue. Koilocytes are epithelial cells characterised by perinuclear haloes surrounding condensed nuclei and are commonly present in cervical intraepithelial neoplasia. Koilocytosis is accepted as pathognomonic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 32 publications
1
50
0
5
Order By: Relevance
“…Human papilloma virions are known to be released when the cornified envelope of cells desquamate; accordingly, HPVs can be transmitted by skin-to-skin contact as well as by sexual activity (Bryan and Brown, 2001). Lawson et al (2009) reported that cell surfaceto-surface contact mainly during sexual activities is required for HPV transmission and modulation of cellular pathways. According to a study, HPV is mainly found on the dermis of the breast and travels through the nipple and ducts, infects the breast tissue and starts the potential malignant process (De Villiers et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Human papilloma virions are known to be released when the cornified envelope of cells desquamate; accordingly, HPVs can be transmitted by skin-to-skin contact as well as by sexual activity (Bryan and Brown, 2001). Lawson et al (2009) reported that cell surfaceto-surface contact mainly during sexual activities is required for HPV transmission and modulation of cellular pathways. According to a study, HPV is mainly found on the dermis of the breast and travels through the nipple and ducts, infects the breast tissue and starts the potential malignant process (De Villiers et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Although p53 degradation is normally mediated by the Mdm2 ubiquitin ligase (34), E6 protein is proposed to bind to E6AP and redirect its specificity to p53 (33,35). Enhanced degradation of p53 in epithelial cells by the HPV16 and -18 viral strains induces cell transformation and development of cervical and oral cancers, depending on the site of infection (5,36,37). Similarly, hepatitis C virus encodes the NS5B protein that binds E6AP and induces degradation of the retinoblastoma protein tumor suppressor, increasing the risk of liver cirrhosis and hepatocellular carcinoma (38,39).…”
Section: E6apmentioning
confidence: 99%
“…About 4-5 m-thick paraffin sections were stained with haematoxylin and eosin, evaluated under a light microscope, and classified according to the WHO classification (17). The existence of koilocytes (nuclear enlargement with clear perinuclear cytoplasmic halo), which were accepted as pathognomonic for HPV (12), was also evaluated.…”
Section: Methodsmentioning
confidence: 99%